2022
DOI: 10.4266/acc.2022.00108
|View full text |Cite
|
Sign up to set email alerts
|

The role of diaphragmatic thickness measurement in weaning prediction and its comparison with rapid shallow breathing index: a single-center experience

Abstract: Background: Acute respiratory failure (ARF) is commonly managed with invasive mechanical ventilation (IMV). The majority of the time that a patient spends on IMV is in the process of weaning. Prediction of the weaning outcome is of paramount importance, as untimely/delayed extubation is associated with a high risk of mortality. Diaphragmatic ultrasonography is a promising tool in the intensive care unit, and its utility in predicting the success of weaning remains understudied. Methods: In this prospective-obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Studies reporting on accuracy to predict weaning outcomes and included in the meta-analysis involved assessment of PImax ( n = 18 studies) [ 24 41 ], diaphragm ultrasound assessments with diaphragm excursion (DE, n = 53 studies) [ 6 , 26 , 30 , 31 , 35 , 37 , 39 – 85 ], diaphragm thickening fraction (DTF, n = 48 studies) [ 38 , 40 , 43 – 56 , 62 , 65 – 67 , 69 , 71 73 , 75 77 , 79 , 81 – 84 , 86 – 101 ] and end-expiratory (Tdi ee , n = 11 studies) [ 45 , 48 , 53 55 , 66 , 73 , 89 , 90 , 99 , 100 ], end-inspiratory diaphragm thickness (Tdi ei , n = 8 studies) [ 48 , 53 55 , 66 , 73 , 89 , 100 ] and P0.1 ( n = 15 studies) [ 25 , 27 , 29 , 36 , 73 , 81 , 102 110 ] (See Additional file 1 : Table S3 for study characteristics). Different weaning outcome definitions were used across studies (Additional file 1 : Table S3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reporting on accuracy to predict weaning outcomes and included in the meta-analysis involved assessment of PImax ( n = 18 studies) [ 24 41 ], diaphragm ultrasound assessments with diaphragm excursion (DE, n = 53 studies) [ 6 , 26 , 30 , 31 , 35 , 37 , 39 – 85 ], diaphragm thickening fraction (DTF, n = 48 studies) [ 38 , 40 , 43 – 56 , 62 , 65 – 67 , 69 , 71 73 , 75 77 , 79 , 81 – 84 , 86 – 101 ] and end-expiratory (Tdi ee , n = 11 studies) [ 45 , 48 , 53 55 , 66 , 73 , 89 , 90 , 99 , 100 ], end-inspiratory diaphragm thickness (Tdi ei , n = 8 studies) [ 48 , 53 55 , 66 , 73 , 89 , 100 ] and P0.1 ( n = 15 studies) [ 25 , 27 , 29 , 36 , 73 , 81 , 102 110 ] (See Additional file 1 : Table S3 for study characteristics). Different weaning outcome definitions were used across studies (Additional file 1 : Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…At least 4 direct comparative studies reporting on accuracy to predict weaning success were found for the following pairs of assessments: DE versus PImax ( n = 8 studies) [ 30 , 31 , 35 , 37 , 39 41 ], DE versus DTF ( n = 28 studies) [ 40 , 43 45 , 47 52 , 54 , 56 , 62 , 65 – 67 , 69 , 71 73 , 75 , 77 , 79 , 81 – 84 , 117 ], DE versus Tdi ee ( n = 5 studies) [ 45 , 48 , 54 , 66 , 73 ], DE versus Tdi ei ( n = 4 studies) [ 48 , 54 , 66 , 73 ], DTF versus Tdi ee ( n = 11 studies) [ 45 , 48 , 53 55 , 66 , 73 , 89 , 90 , 99 , 100 ], DTF versus Tdi ei ( n = 8 studies) [ 48 , 54 , 55 , 66 , 73 , 89 , 100 ] and P0.1 versus PImax ( n = 4 studies) [ 25 , 27 , 29 , 36 ]. The SROC curves estimated based on direct comparative studies are presented in Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One study included patients with complicated weaning (who had failed previous attempts of SBT) 3 and one study included patients at high risk of extubation failure 42 . Some studies focused exclusively on patients with chronic obstructive pulmonary disease (COPD) 5 or COVID‐19 41 or patients whose intubation was due to respiratory causes 28,29,36,39 . This aspect could compromise the applicability of the results due to patient selection.…”
Section: Resultsmentioning
confidence: 99%
“…Diaphragmatic dysfunction was assessed by DE in six studies, DTF in five and both in nine studies. Seven studies compared diaphragmatic US with other methods that have been previously used to predict successful extubation in the ICU: rapid shallow breathing index (RSBI) 33,34,36,37 and Lung US score 11,34,37 in four and three studies, respectively.…”
Section: Baseline Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation